Vanilla cultivation in Mexico: Typology, characteristics, production, agroindustrial prospective and biotechnological innovations as a sustainability strategy (Scientia Agropecuaria, 2023)
Vanilla is the orchid of greatest economic interest to the world since the spice of the same name is obtained from it. Vanillin is obtained from its ripened pod, this compound is highly recognized and demanded by the gastronomic, pharmaceutical, and cosmetic industries for the sweet aroma and flavor it emanates. The objective of this work was to carry out a literature review to put into perspective the reader about the sustainability strategies in the vanilla industry in Mexico, as well as the innovations of propagation and in vitro conservation of Vanilla planifolia germplasm. Despite being originally from Mexico, this country ranks third in world production, preceding Madagascar, and Indonesia. This compilation of studies presents biotechnological techniques to increase vanilla production, as well as alternatives that can reduce the negative effects caused by the low genetic accumulation in this species, such as plant tissue culture, use of molecular markers for the study of somaclonal variation, asymbiotic seed germination under in vitro conditions. These techniques together with agro-industrial strategies can represent a sustainable alternative for vanilla production. In this article, strategies are suggested that allow those interested in vanilla production to make appropriate decisions, however, it is necessary to develop multidisciplinary studies that allow a global approach to the phenomena involved in the production and use of vanilla, as well as the resolution of the problems that this process faces.
Keywords: Biotechnological alternative; Micropropagation; In vitro culture; Temporary Immersion Systems